Exploring opportunities of taurit in wastewater treatment (Experimental biology, 2015)
The article covers the sewage treatment from heavy metals using natural sorbents, such as taurit. The possibilities of using taurit for the treatment of wastewater contaminated with aluminum are given in the experimental data. It was found that taurit has modulating effect on the quality of water that is accompanied by improvement of hydrological indicators, reducing the concentration of aluminum in water and decreases its cytotoxicity.
Keywords: taurit; sorbent; aluminum; sewage